Peripheral Pneumatic Dissection and Scar Peeling to Complete Deep Anterior Lamellar Keratoplasty in Eyes With Healed Hydrops. Issue 4 (April 2019) - Goweida, Mohamed Bahgat; Sobhy, Mohamed; Seifelnasr, Mohamed; Liu, Christopher
Abstract : Purpose: To describe a surgical technique to achieve the desired plane during deep anterior lamellar keratoplasty (DALK) in eyes with Descemet membrane (DM) tears due to previous hydrops. Methods: This was a prospective, consecutive, interventional case series of DALK in 12 keratoconic eyes with healed hydrops. Dissection of the peripheral cornea was performed by air injection and using the microbubble incision technique as a guide to the clear predescemetic stroma. The central posterior scar was then removed by peeling to bare DM. Results: DALK was successfully completed in all eyes, with DM tears ranging from a microperforation to approximately 4 mm. At 12 months, the mean logMAR best-corrected visual acuity was 0.38 ± 0.07, the mean keratometric astigmatism was 5.2 ± 1.9 diopters, and the mean endothelial cell density was 2364 ± 316.9 cells/mm 2 . Conclusions: Peripheral pneumatic dissection and central scar peeling technique is a useful technique to complete DALK in eyes with scars due to previous hydrops. Abstract : Supplemental Digital Content is Available in the Text.